Implications of Crop Rotation and Fungicide on Fusarium and Mycotoxin Spectra in Manitoba Barley, 2017–2019 - M. Nazrul Islam; Mitali Banik; Srinivas Sura; James R. Tucker; Xiben Wang (Toxins, 2022)
Fusarium head blight (FHB) is one of the most important diseases of barley in Manitoba province (western Canada), and other major barley producing regions of the world. Little is known about the Fusarium species and mycotoxin spectra associated with FHB of barley in Manitoba. Hence, barley grain samples were collected from 149 commercial fields from 2017 to 2019, along with information on respective cropping history, and analyzed with respect to Fusarium species spectra, abundance, chemotype composition, and mycotoxin profiles. Fusarium poae was the predominant Fusarium species associated with FHB of barley in Manitoba, followed by F. graminearum, and F. sporotrichioides; F. equiseti and F. avenaceum were also detected but at low levels. F. poae strains with the nivalenol (NIV) chemotype and F. graminearum strains with 3-acetyl deoxynivalenol (3-ADON) and 15-acetyl deoxynivalenol (15-ADON) chemotypes were commonly detected in the barley grain samples. Nivalenol (597.7, 219.1, and 412.4 µg kg−1) and deoxynivalenol (DON) (264.7, 56.7, and 65.3 µg kg−1) were the two most prevalent mycotoxins contaminating Manitoba barley in 2017, 2018 and 2019, respectively. A substantially higher DON content was detected in grain samples from barley fields with cereals as a preceding crop compared to canola and flax. Furthermore, F. poae proved less sensitive to four triazole fungicides (metconazole, prothioconazole+tebuconazole, tebuconazole, and prothioconazole) than F. graminearum. Findings from this research will assist barley producers with improved understanding of FHB threat levels and optimizing practices for the best management of FHB in barley.